Juvéderm Volift (VYC-17.5L), a Hyaluronic Acid Filler with Lidocaine, is Safe and Effective for Correcting Nasolabial Folds in Chinese Subjects - Xie Y; Li Q; Gao Z; Sun J; Li D; Harvey C; Qu J; Snow S; Li Q (Dove Medical Press, 2022)
Yun Xie,1 Qin Li,2 Zhanwei Gao,3 Jiaming Sun,4 Dong Li,5 Candice Harvey,6 Jiazhi Qu,7 Sean Snow,8 Qingfeng Li1 1Plastic Surgery Department of Shanghai 9th People's Hospital, Shanghai, People's Republic of China; 2Plastic Surgery Department of General Hospital of Guangzhou Military Command of PLA, Guangzhou, Guangdong, People's Republic of China; 3Plastic Surgery Department of Japan Friendship Hospital, Chaoyang, Beijing, People's Republic of China; 4Plastic Surgery Department of Union Hospital Tongji Medical College Huazhong University of Science and Technology, Wuhan, Hubei, People's Republic of China; 5Plastic Surgery Department of Peking University Third Hospital, Haidian, Beijing, People's Republic of China; 6Allergan Aesthetics, an AbbVie Company, Marlow, UK; 7Allergan Aesthetics, an AbbVie Company, Beijing, People's Republic of China; 8Allergan Aesthetics, an AbbVie Company, Irvine, CA, USACorrespondence: Qingfeng Li, Shanghai 9th People's Hospital, No. 639, Zizaoju Road, Shanghai, 200011, People's Republic of China, Tel + 86-21-53315615, Fax + 86-21-63089567, Email dr.liqingfeng@yahoo.comPurpose: Hyaluronic acid injectable gels are commonly used to treat nasolabial folds (NLFs). We evaluated the safety and effectiveness of VYC-17.5L for correcting NLFs in Chinese subjects.Patients and Methods: This prospective, multicenter, double-blind, within-subject‒controlled study randomized adults with moderate-to-severe NLFs to VYC-17.5L treatment (initial and touch-up) in 1 NLF and control (without lidocaine) in the contralateral NLF. Effectiveness endpoints at 6 months included noninferiority of VYC-17.5L to control in NLF Severity Scale response rate (primary endpoint), subject-reported procedural pain (11-point scale), and investigator and subject assessments using the Global Aesthetic Improvement Scale (GAIS).Results: A total of 175 subjects were included. The primary endpoint was met, with response rates of 84.2% for VYC-17.5L and 82.5% for control. Mean pain scores after initial and touch-up treatments were 2.4 for VYC-17.5L versus 5.2 for control (P < 0.001) and 2.0 versus 3.3 (P < 0.001), respectively. Investigator-rated GAIS scores were 86.5% for VYC-17.5L versus 86.0% for control. There were no between-group differences in subject-rated GAIS scores. Safety profiles were comparable for VYC-17.5L and control.Conclusion: VYC-17.5L was noninferior to control without lidocaine for correcting moderate-to-severe NLFs in Chinese subjects and was superior to control in reducing procedural pain.Keywords: hyaluronic acid, dermal fillers, lidocaine